Design and Development of Liposome by Microencapsulation Vesicle Method and Vaginal Delivery System for Fluconazole Gel In-Vitro Diffusion Study - Patel, Arun (International Journal of Pharmaceutical & Biological Archive, 2016)
Design and Development of Liposome by Microencapsulation Vesicle Method and Vaginal Delivery System for Fluconazole Gel In Vitro Diffusion Study